A longitudinal study on new onset anxiety among children and adolescents during the COVID-19 epidemic - WANG Xiaoyu; PENG Yinhui; MA Wenlin; YAO Boshuang; LI Yifan; ZHAO Li; YANG Chunxia (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2023)
Objective·To investigate the occurrence of new onset anxiety symptoms in children and adolescents during the COVID-19 epidemic, and analyze the influencing factors.Methods·Based on Chengdu Positive Child Development (CPCD) cohort, a total of 5 566 children and adolescents from five primary and secondary schools in Chengdu were enrolled. Two longitudinal study cohorts of new anxiety symptoms in children and adolescents were established, and two rounds of survey were conducted. The first round of survey (baseline survey) was conducted from December 2019 to January 2020, and the general demographic characteristics of the cohort members were collected through the Student Questionnaire for the Study on Promoting Positive Growth of Children and Adolescents. The second round of survey (follow-up survey) was conducted from February to July 2020 to collect additional information on the cohorts' infection history of COVID-19, and whether their eating, learning, and social and recreational activities were affected by the COVID-19 epidemic. The Screen for Child Anxiety Related Emotional Disorders (SCARED) was used to evaluate the new onset anxiety symptoms of all subjects. The multivariate Logistic regression model was used to analyze the influencing factors of new onset anxiety symptoms in children and adolescents.Results·The results of SCARED assessment showed that the incidence of new onset anxiety symptoms among children and adolescents in Chengdu during the COVID-19 epidemic was 13.47%. In the longitudinal study cohort of new onset anxiety in children,the incidence was 11.91%, and in the longitudinal study cohort of new onset anxiety in adolescents, the incidence was 14.25%. The results of chi square test showed that there were statistically significant differences in the incidence of new onset anxiety symptoms among children in terms of age, whether they or their family members were infected with COVID-19, and whether their eating, learning and social activities were affected (all P<0.05); there were also statistically significant differences in the incidence of new onset anxiety symptoms among adolescents in gender, grade, age, residential area, and whether their eating, learning, and social and recreational activities were affected (all P<0.05). The results of multivariate Logistic regression analysis showed that, for children, 6‒8 years old was the protective factor for their new onset anxiety symptoms, while they or their family members infected with COVID-19 and the impact of their learning activities were the risk factors (all P<0.05); for adolescents, males, residing in urban areas, and grades ≤ 6 were the protective factors for their new onset anxiety symptoms, while the impact of their learning activities was the risk factor (all P<0.05).Conclusion·For children and adolescents, the factors that affect their new onset anxiety symptoms during the COVID-19 epidemic are not completely the same. For children, age, whether they or their family members are infected with COVID-19, and whether their learning is affected are independent influencing factors; but for adolescents, gender, grade, residential area, and whether their learning is affected are independent influencing factors. Therefore, in the process of dynamically paying attention to the mental health status of children and adolescents and continuously doing a good job of mental health intervention, it is necessary to follow the law of growth, fully consider the developmental characteristics of children and adolescents, and adopt different strategies and measures.